Folate cycle genetics, level of homocysteine, thyroid and pituitary hormones in the blood among the children from the districts bordering the Chornobyl exclusion zone (Environment & Health, 2021)
Objective: The aim of the study was to identify interrelations between the state of folate cycle genetic apparatus and blood levels of homocysteine, thyroid and adenohypophysis hormones in the blood among the children from Ivankivskyi and Poliskyi districts, Kyiv region, bordering the Chornobyl exclusion zone (СhEZ).Methods: Immunochemical, genetic, statistical ones.Results: We measured blood levels of homocysteine (Hcy), pituitary thyroid-stimulating hormone (TSH), free triiodothyronine (T3), free thyroxine (T4) in 158 children from Poliskyi district and 178 children from Ivankivskyi district and assessed the state of a genetic system of the folate cycle (FC). The average age of the examined was (15.2 ± 0.9) years old (95% CI 15.0-15.4 years old). Taking into account the FC genotypes, genetic subgroups were formed, they were based on 100% representation of one specific genotype. The laboratory examination was carried out twice: in April and December 2015 (before and after the fires in the ChEZ). It was found out that in the total group of the children, as well as in most of analyzed genetic subgroups, the level of Hcy and thyroid hormones (TG) in the children from Ivankivskyi district was statistically significantly higher than in those from Poliskyi district. At the same time, a direct association between Hcy and TSH was observed in the total group, as well as in most of the genetic subgroups of children from Ivankivskyi district, and this ssociation was absent in the children from Poliskyi district. The blood level of Hcy both in the children from Poliskyi district and in the children from Ivankivskyi district was statistically significantly higher in the subgroup containing only homozygous variants of the T allele of the MTHFR:677 genetic polymorphism in comparison with the subgroups containing neutral C alleles of the same polymorphism. At the same time, there were no differences for TSH, T3 and T4.Сonclusions: The analysis enabled to establish a synchronous reaction of metabolic cycles ensuring the metabolism of Hcy and thyroid hormones in the adolescents, regardless of the FC genotypes. Correlation analysis, as well as the results of statistical analysis, indicate that an increase in the level of Hcy in the blood of children induced the synthesis of TSH and T3. The results show a close relationship between thyroid hormone genesis and the metabolism of methionine sulfur-containing amino acids and Hcy. A forest fire, containing long-lived radioactive elements, is the most likely reason for the increase of Hcy level and, as a result, the hormones of the pituitary-thyroid axis in the blood of the children living in the districts, bordering the ChEZ.
Keywords: homocysteine; folate cycle; thyroid and pituitary hormones; adolescents; radiation contaminated areas